Implementation of Fuzzy Logic controller in Photovoltaic Power generation using Boost Converter and Boost Inverter - Abubakkar Siddik A; Shangeetha M (Institute of Advanced Engineering and Science, 2012)
Increasing in power demand and shortage of conventional energy sources, researchers are focused on renewable energy. The proposed solar power generation circuit consists of solar array, boost converter and boost inverter. Low voltage, of photovoltaic array, is boosted using dc-dc boost converter to charge the battery and boost inverter convert this battery voltage to high quality sinusoidal ac voltage. The output of solar power fed from boost inverter feed to autonomous load without any intermediate conversion stage and a filter. For boost converter operation duty cycle is varied through fuzzy logic controller and PWM block to regulate the converter output voltage. The ac voltage total harmonic distortion (THD) obtained using this configuration is quite acceptable. The proposed power generation system has several desirable features such as low cost and compact size as number of switches used, are limited to four as against six switches used in classical two-stage inverters.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.334